China and the steppe: reception and resistance. (4th April 2017) - Rawson, Jessica
Abstract: Abstract : The development of several key technologies in China—bronze and iron metallurgy and horse-drawn chariots—arose out of the relations of central China, of the Erlitou period ( c. 1700–1500 BC), the Shang ( c. 1500–1046 BC) and the Zhou (1046–771 BC) dynasties, with their neighbours in the steppe. Intermediaries in these exchanges were disparate groups in a broad border area of relatively high land around the heart of China, the Central Plains. The societies of central China were already so advanced that, when these foreign innovations were adopted, they were transformed within highly organised social and cultural systems.